Effective the flexibility developments of smashstroke in - Mhows, Riaad (Journal of Physical Education, 2009)
the search goals is knowing the effect of training program to develop smash stroke in serve skill in tennis by use the practical way and equal group where chooses randomly. the sample of research where from 4th sport collage 30 student experimental group (15), control group (15). the program is taking (8) weeks with 16 untie8 weeks with 16 untie the time of each is (90) mints, the results are the program is developing the flexibility of smash stroke in tennis therefore Effective developments tennis serve